2014
DOI: 10.2147/ccid.s44843
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and comorbidities: links and risks

Abstract: Psoriasis is a chronic inflammatory skin disease affecting approximately 2% of the population worldwide. In the past decade, many studies have drawn attention to comorbid conditions in psoriasis. This literature review examines the epidemiological evidence, pathophysiological commonalities, and therapeutic implications for different comorbidities of psoriasis. Cardiovascular disease, obesity, diabetes, hypertension, dyslipidemia, metabolic syndrome, nonalcoholic fatty liver disease, cancer, anxiety and depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 191 publications
(206 reference statements)
0
39
1
1
Order By: Relevance
“…The permanent chronic inflammatory state associated with these comorbidities may lead to an increased risk of cardiovascular morbidity and mortality [34,35,36]. Thus, severe psoriasis is associated with an elevated risk of cardiovascular disease and myocardial infarction [13]. There is evidence that patients with moderate to severe psoriasis and patients with previous systemic treatment seem to be at a higher risk of obesity and, as a consequence, of cardiovascular disease than patients with mild disease [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The permanent chronic inflammatory state associated with these comorbidities may lead to an increased risk of cardiovascular morbidity and mortality [34,35,36]. Thus, severe psoriasis is associated with an elevated risk of cardiovascular disease and myocardial infarction [13]. There is evidence that patients with moderate to severe psoriasis and patients with previous systemic treatment seem to be at a higher risk of obesity and, as a consequence, of cardiovascular disease than patients with mild disease [37].…”
Section: Discussionmentioning
confidence: 99%
“…The discussion of potential reasons for our epidemiological observations should include the inflammatory process in the adipose tissue as an endocrine organ [9,10,11,12,13,14], the genetic predisposition to develop obesity together with altered lifestyle habits. It has been shown that HLA-Cw6, the most important gene susceptibility locus for psoriasis, is also associated with obesity: obese patients carrying HLA-Cw6 were 35 times more likely to develop psoriasis than HLA-Cw6-negative patients of normal weight [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different environmental triggers like infection (from bacteria, fungi and viruses) [2,3], medications (lithium, antimalarials and nonsteroidal anti-inflammatory drugs) [2,4,5], obesity [6] and stress [7] initiate or worsen this complex, multifactorial syndrome in genetically prone individuals. Ps patients are at a great risk of developing a number of comorbid conditions including diabetes mellitus, hypertension, coronary heart disease, inflammatory bowel disease, lymphoma and depression [8]. In addition, disorders involving musculoskeletal structures, the eyes and the gut are also common in these patients [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is known to have a number of different comorbidities, as shown in a study by Ni and Chiu [68], such as cardiovascular disease, obesity, diabetes, hypertension, dyslipidemia, metabolic syndrome, nonalcoholic fatty liver disease, cancer, anxiety and depression, and inflammatory bowel disease. Inflammatory bowel disease was found to be at a higher prevalence in psoriasis patients compared to the general population.…”
Section: Bidirectional Inflammatory and Neurochemical Phenomenonmentioning
confidence: 99%